2010
DOI: 10.1183/09031936.00044710
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D levels and exercise-induced bronchoconstriction in children with asthma

Abstract: Epidemiological studies have established a relationship between low levels of serum vitamin D and reduced lung function in healthy adults, and asthma onset and severity in children. However, no study has examined the relationship between vitamin D levels and exercise-induced bronchoconstriction in asthmatic children.We evaluated the relationship between 25-hydroxyvitamin D concentrations and baseline forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1) and change in FEV1 (DFEV1) after a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 43 publications
7
77
0
4
Order By: Relevance
“…Multiple previous studies have found that inhaled corticosteroids improve lung function (16). Our finding that children who are vitamin D deficient are more likely to have lower lung function is consistent with a previous study that demonstrated that in children with exerciseinduced bronchoconstriction, lower vitamin D levels were associated with reduced lung function (17). Our study's result that children with asthma who are vitamin D sufficient have improved lung function is also supported by other studies.…”
Section: Discussionsupporting
confidence: 82%
“…Multiple previous studies have found that inhaled corticosteroids improve lung function (16). Our finding that children who are vitamin D deficient are more likely to have lower lung function is consistent with a previous study that demonstrated that in children with exerciseinduced bronchoconstriction, lower vitamin D levels were associated with reduced lung function (17). Our study's result that children with asthma who are vitamin D sufficient have improved lung function is also supported by other studies.…”
Section: Discussionsupporting
confidence: 82%
“…Alyasin ve ark.nın (31) çalışmasında D vitamini düzeylerinde düşüklük ile astım şiddeti ve hastaneye yatma oranları arasında bizim çalışma sonuçlarımızın aksine bir ilişki saptanmadı. Bu sonuç da onların çalışma grubunun yaş aralığının (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) …”
Section: Astımlı çOcuklar Ve Kontrol Grubunun Laboratuvar Sonuçlarıunclassified
“…Bazı kesitsel çalışmalarda serum D vitamini düzeylerinin astımlı çocuklarda sağlıklı çocuklara göre daha düşük olduğu (4,(10)(11)(12) sınırlı sayıdaki çalışmada serum D vitamini düzeylerindeki yüksekliğinin astım riskinde artmaya neden olduğu gösterilmiştir (13,14). Bazı çalışmalarda ise bu farklılıklar gözlenmemiştir (15)(16)(17)(18)(19). D vitamini ve günümüzdeki astım rehberlerinde astım tedavisinin ana amacı olarak ifade edilen astım kontrolü ilişkili yapılmış sınırlı sayıda çalışma vardır.…”
Section: Introductionunclassified
“…15 Other studies have shown that low serum vitamin D levels are associated with reduced lung function in adolescents, 16 poor asthma control, 17 and the presence of exercise-induced bronchoconstriction in children with asthma. 18 A recent study showed increased levels of vitamin D-binding protein and 25-hydroxyvitamin D in bronchoalveolar lavage fluid after allergen challenge, suggesting a role for these factors in allergic late-phase reactions. 19 A low serum vitamin D level may represent a marker of Western life style.…”
Section: Introductionmentioning
confidence: 99%